Forging process of ferritic stainless steel

By controlling the forging temperature and deformation amount, refining the grains, and controlling the annealing and furnace cooling process, the problem of 0Cr13 stainless steel forming brittle ferrite and carbide precipitation under high temperature conditions was solved, and the impact performance and comprehensive performance of the material were significantly improved.

CN119640011APending Publication Date: 2025-03-18WUXI PAIKE HEAVY CASTING & FORGING
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411840124.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

0Cr13 stainless steel is prone to form brittle ferrite δ-Fe under high temperature conditions and precipitation of grain boundary carbides during cooling, which affects the overall performance of the material, especially the impact performance.

Method used

By controlling the forging temperature below the 0Cr13 ferrite/austeinite transition temperature, the δ-ferrite generation of brittle tissue is reduced; the forging ratio is ≥4, the single deformation of the forging length is 2-5mm, the total deformation is 40-60%, and the grain is refined; the insulation coefficient is controlled at about 1min/mm, reducing the annealing time and furnace cooling speed, and avoiding the precipitation of brittle carbides.

Benefits of technology

The impact performance of 0Cr13 stainless steel is significantly improved, with room temperature impact ≥100J, hardness 145~186HB, tensile strength Rm≥480MPa, yield strength Rp0.2 is 280~410MPa, elongation ≥35%, and cross-section shrinkage ≥72.7%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640011A_ABST
    Figure CN119640011A_ABST
Patent Text Reader

Abstract

The invention relates to a forging process of ferritic stainless steel, which comprises the following steps of: forging and heating: heating a test bar to 1100-1130 DEG C along with a furnace, preserving heat for 1-2 hours, discharging and forging; forging: drawing out the test bar to a set size; cooling after forging: performing air cooling to 350-500 DEG C after forging; and annealing is conducted, specifically, the temperature is increased to 850-870 DEG C according to power, heat preservation is conducted, the heat preservation coefficient is calculated according to the conditions that through heating is conducted for 1 h and the structure transformation rate is 1 min / mm, furnace cooling is conducted to 600-700 DEG C, then discharging is conducted, water cooling is conducted for 1-2 min, and a forged piece is obtained According to the forging process of the ferritic stainless steel, (1) precipitation of a brittle structure delta-ferrite is reduced by controlling the forging temperature to be lower than the 0Cr13 ferrite / austenite transformation temperature; and (2) by increasing the deformation amount, the process of single-time small drawing-out amount and multi-time drawing-out is adopted, so that forging cracks are reduced, grains are refined, and an excellent original structure is provided for heat treatment. And 3) reducing precipitation of brittle carbides and rapidly cooling to avoid a 475 DEG C brittle zone by reducing annealing heat preservation time and discharging and water-cooling after furnace cooling, so as to improve the impact property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of steel forging, and in particular to a forging process of ferrite stainless steel. Background Art

[0002] 0Cr13 stainless steel has been widely used in gas turbine parts and other fields due to its excellent corrosion resistance and plastic toughness. However, in the actual production process, especially under high temperature conditions, 0Cr13 stainless steel is prone to form ferrite δ-Fe and grain boundary carbide precipitation during cooling, which will affect the comprehensive properties of the material, especially the impact resistance.

[0003] The generation of high temperature ferrite phase and the precipitation of carbides at grain boundaries during cooling have always been obstacles to the impact performance of non-austenitic stainless steel. People usually use the following methods:

[0004] 1) Regulating ingredients: It is generally believed in the industry that C, Mn, and Ni are elements that inhibit the formation of ferrite, and Cr and Si are elements that form ferrite. If you want to reduce the impact of δ-Fe on performance, you should reduce the content of Cr and Si, and increase the content of C, Mn, and Ni. At the same time, practice has found that when the content of C and N is too small, the production cost of the product will increase significantly and it is not conducive to the improvement of strength; when the content of C and N is too large, the plasticity, toughness, corrosion resistance, and welding performance of the material are prone to significant deterioration. When the content of Mn is too small, it is not conducive to the stability of the material's strength performance; when the content of Mn is too large, it is easy to cause a sharp deterioration in the plasticity and toughness of the material.

[0005] 2) Temperature control: It is generally believed that lowering the forging temperature can significantly reduce the precipitation of δ-Fe and increasing the tempering temperature can effectively improve the impact properties.

[0006] 3) Regulating the organization: It is generally believed that the ferrite phase has a body-centered cubic structure with low plasticity and toughness. Increasing the residual austenite and martensite phases in the organization is beneficial to improving the impact properties of the material.

[0007] However, the above methods usually increase production costs and make it difficult to obtain stable and ideal tissues.

[0008] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention

[0009] In view of the deficiencies in the prior art, an embodiment of the present invention discloses a forging process for ferritic stainless steel to solve the problems of high production cost and poor plasticity and toughness of ferritic stainless steel.

[0010] The technical solution adopted by the present invention is as follows:

[0011] A forging process of ferritic stainless steel comprises the following steps: forging heating: heating a test bar to 1100-1130°C with a furnace, keeping the temperature for 1-2 hours and then taking it out of the furnace for forging; forging: drawing the test bar to a set size; cooling after forging: air cooling to 350-500°C after forging; annealing: heating to 850-870°C according to power and keeping the temperature, the insulation coefficient is calculated according to heat penetration of 1 hour and microstructure transformation rate of 1 min / mm, cooling the furnace to 600-700°C and then taking it out of the furnace for water cooling for 1-2 minutes to obtain a forged piece.

[0012] By calculating the fixed temperature phase distribution phase transformation diagram through J Mat Pro, it can be found that 1150℃ is the ferrite / austenite transformation temperature of 0Cr13. Therefore, the forging temperature is reduced to 1130℃ to reduce the phase transformation stress caused by the formation of brittle structure δ-ferrite and cause cracking. The Ms point of 0Cr13 stainless steel is 315-321℃. After forging, it is air-cooled to above the Ms point, inheriting the forged structure, and then fully annealed to achieve the structure transformation. The annealing temperature is 30℃ above the Ac1 point, which does not change the ferrite morphology distribution in the original structure, and the carbide spheroids are dispersed. By reducing the annealing time, the insulation coefficient is controlled at about 1min / mm, reducing the precipitation of carbides at the grain boundaries and improving the impact performance.

[0013] A further technical solution is that during the forging process, the forging ratio is ≥4, so as to fully forge core defects, break up the original structure and refine the grains.

[0014] The further technical solution is that the single deformation of forging and drawing is 2 to 5 mm, and the total deformation is 40 to 60%. By refining the austenite deformation structure, it is ensured that fine grains are obtained in the subsequent heat treatment process, so that the impact toughness of stainless steel can be greatly improved on the basis of obtaining higher strength and plasticity.

[0015] A further technical solution is to round the steel bar after each forging and stretching process to avoid cracks at the edges and corners and reduce the risk of cracking.

[0016] A further technical solution is that the furnace cooling rate is 50-80°C / h. The furnace cooling can promote the dispersion of spherical tungsten carbide, which is a good diffusion, and avoid the 475°C brittle zone through rapid cooling.

[0017] A further technical solution is that the chemical composition of the 0Cr13 stainless steel is as follows by weight percentage: C: ≤0.30%; Si: 0.40-0.80%; Mn: 0.30-1.00%; P: ≤0.30%; S: ≤0.30%; Cr: 11.50-13.50%; Al: ≤0.030%; the remainder is Fe and unavoidable impurities.

[0018] A further technical solution is that the chemical composition of the 0Cr13 stainless steel is as follows by weight percentage: C: 0.07-0.08%; Si: 0.56-0.61%; Mn: 0.48-0.53%; P: 0.021-0.023%; S: 0.001-0.004%; Cr: 11.76-12.60%; Al: 0.006-0.01%; the remainder is Fe and unavoidable impurities.

[0019] A further technical solution is that the metallographic structure of the forging is ferrite and bainite, and the grain size is 6 to 8 levels.

[0020] A further technical solution is that the room temperature impact of the prepared 0Cr13 ferrite stainless steel is ≥100J, the hardness is 145-186HB, the tensile strength Rm is ≥480MPa, the yield strength Rp0.2 is 280-410MPa, the elongation is ≥35%, and the cross-sectional shrinkage is ≥72.7%.

[0021] The beneficial effects of the embodiments of the present invention are as follows:

[0022] (I) The forging process of ferritic stainless steel of the present invention comprises the following steps: forging heating: heating the test bar with the furnace to 1100℃~1130℃, keeping the temperature for 1~2h and then forging out of the furnace; forging: drawing the test bar to the set size; cooling after forging: air cooling to 350~500℃ after forging; annealing: heating to 850~870℃ according to power and keeping the temperature, the insulation coefficient is calculated according to the heat penetration of 1h and the microstructure transformation rate of 1min / mm, cooling the furnace to 600~700℃ and then cooling the furnace out of the furnace for 1~2min to obtain the forging. The forging has excellent performance, stainless steel room temperature impact ≥100J, hardness of 145~186HB, tensile strength Rm≥480MPa, yield strength Rp0.2 of 280~410MPa, elongation ≥35%, and section shrinkage ≥72.7%.

[0023] (ii) The forging process of the ferritic stainless steel of the present invention, 1) by controlling the forging temperature to be lower than the ferrite / austenite transformation temperature of 0Cr13, the precipitation of brittle structure δ-ferrite is reduced. 2) During the forging process, the forging ratio is ≥4, the single deformation of forging drawing is 2-5mm, and the total deformation is 40-60%. By increasing the deformation, the process of single small drawing amount + multiple drawing is adopted to reduce forging cracking and refine the grains, providing excellent original structure for heat treatment. 3) The thermal insulation coefficient is calculated based on 1h of heat penetration and 1min / mm of structure transformation rate. By reducing the annealing insulation time + furnace cooling and water cooling after furnace cooling, the precipitation of brittle carbides is reduced and rapid cooling is performed to avoid the 475℃ brittle zone to improve the impact performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The forging process of the ferritic stainless steel of the present invention is a flow chart.

[0025] Figure 2 The metallographic result of the forging ×200 obtained in the first embodiment of the present invention.

[0026] Figure 3 The metallographic result of the forging ×1000 obtained in the first embodiment of the present invention.

[0027] Figure 4 The metallographic result of the forging ×200 obtained in the second embodiment of the present invention.

[0028] Figure 5 The metallographic result of the forging ×200 obtained in the third embodiment of the present invention.

[0029] Figure 6 The metallographic results of forgings × 200 were obtained for the comparative example of the present invention. DETAILED DESCRIPTION

[0030] The specific implementation of the present invention will be described below in conjunction with the accompanying drawings.

[0031] In order to make the purpose, technical scheme and advantages of the present invention clearer, the device proposed by the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. According to the following description, the advantages and features of the present invention will be clearer. It should be noted that the accompanying drawings adopt a very simplified form and use non-precise proportions, which are only used to conveniently and clearly assist in explaining the purpose of the embodiments of the present invention. In order to make the purpose, features and advantages of the present invention more obvious and easy to understand, please refer to the accompanying drawings. It should be noted that the structure, proportion, size, etc. illustrated by the accompanying drawings of this specification are only used to match the content disclosed in the specification for people familiar with this technology to understand and read, and are not used to limit the limiting conditions for the implementation of the present invention, so they have no technical substantive significance. Any modification of the structure, change of the proportional relationship or adjustment of the size, without affecting the effect that the present invention can produce and the purpose that can be achieved, should still fall within the scope of the technical content disclosed by the present invention.

[0032] First embodiment:

[0033] A forging process for ferritic stainless steel comprises the following steps:

[0034] Step S1, forging heating: heating the test bar to 1120°C in the furnace, keeping the temperature for 1.5 hours and then taking it out of the furnace for forging.

[0035] Specifically, a Φ25*300mm test bar is used. The chemical composition of 0Cr13 stainless steel is as follows by weight percentage: C: 0.07%; Si: 0.60%; Mn: 0.48%; P: 0.022%; S: 0.002%; Cr: 12.26%; Al: 0.009%; the remainder is Fe and unavoidable impurities.

[0036] Step S2, forging: drawing the test rod to a set size.

[0037] Specifically, a Φ25*300mm test bar is forged into a Φ20*600mm long test bar, and each forging and stretching is followed by rounding. During the forging process, the forging ratio is ≥4, the single deformation of the forging and stretching is 2-5mm, and the total deformation is 40-60%.

[0038] Step S3, cooling after forging: air cooling to 400°C after forging and annealing in a furnace.

[0039] Step S4, annealing: heating to 860°C according to power, thermal insulation coefficient calculated according to heat penetration of 1h and microstructure transformation rate of 1min / mm, furnace cooling to 650°C and then water cooling for 1.5min to obtain forgings.

[0040] Specifically, the holding time is 1.5 h, and the furnace cooling rate is 65° C. / h.

[0041] Second embodiment:

[0042] A forging process for ferritic stainless steel comprises the following steps:

[0043] Step S1, forging heating: heating the test bar to 1100°C in the furnace, keeping the temperature for 2 hours and then taking it out of the furnace for forging.

[0044] Specifically, a Φ25*300mm test bar is used. The chemical composition of 0Cr13 stainless steel is as follows by weight percentage: C: 0.08%; Si: 0.56%; Mn: 0.50%; P: 0.023%; S: 0.001%; ​​Cr: 12.60%; Al: 0.006%; the remainder is Fe and unavoidable impurities.

[0045] Step S2, forging: drawing the test rod to a set size.

[0046] Specifically, a Φ25*300mm test bar is forged into a Φ20*600mm long test bar, and each forging and stretching is followed by rounding. During the forging process, the forging ratio is ≥4, the single deformation of the forging and stretching is 2-5mm, and the total deformation is 40-60%.

[0047] Step S3, cooling after forging: air cooling to 350°C after forging and annealing in a furnace.

[0048] Step S4, annealing: heating to 850°C according to power, thermal insulation coefficient calculated according to heat penetration of 1h and microstructure transformation rate of 1min / mm, furnace cooling to 600°C and then water cooling for 1min to obtain forgings.

[0049] Specifically, the holding time is 1.5 h, and the furnace cooling rate is 50° C. / h.

[0050] Third embodiment:

[0051] A forging process for ferritic stainless steel comprises the following steps:

[0052] Step S1, forging heating: heating the test bar to 1130°C in the furnace, keeping the temperature for 1 hour and then taking it out of the furnace for forging.

[0053] Specifically, a Φ25*300mm test bar is used. The chemical composition of 0Cr13 stainless steel is as follows by weight percentage: C: 0.08%; Si: 0.61%; Mn: 0.53%; P: 0.021%; S: 0.001%; ​​Cr: 12.07%; Al: 0.01%; the remainder is Fe and unavoidable impurities.

[0054] Step S2, forging: drawing the test rod to a set size.

[0055] Specifically, a Φ25*300mm test bar is forged into a Φ20*600mm long test bar, and each forging and stretching is followed by rounding. During the forging process, the forging ratio is ≥4, the single deformation of the forging and stretching is 2-5mm, and the total deformation is 40-60%.

[0056] Step S3, cooling after forging: air cooling to 500°C after forging and annealing in a furnace.

[0057] Step S4, annealing: heating to 870°C according to power, thermal insulation coefficient calculated according to heat penetration of 1h and microstructure transformation rate of 1min / mm, furnace cooling to 700°C and then water cooling for 2min to obtain forgings.

[0058] Specifically, the holding time is 1.5 h, and the furnace cooling rate is 80° C. / h.

[0059] Comparative Example:

[0060] A forging process for ferritic stainless steel comprises the following steps:

[0061] Step S1, forging heating: heating the test bar to 1180°C in the furnace, keeping the temperature for 1.5 hours and then taking it out of the furnace for forging.

[0062] Specifically, a Φ25*300mm test bar is used. The chemical composition of 0Cr13 stainless steel is as follows by weight percentage: C: 0.07%; Si: 0.57%; Mn: 0.50%; P: 0.022%; S: 0.002%; Cr: 12.20%; Al: 0.008%; the remainder is Fe and unavoidable impurities.

[0063] Step S2, forging: drawing the test rod to a set size.

[0064] Specifically, a Φ25*300mm test bar is forged into a Φ20*600mm long test bar, and each forging and stretching is followed by rounding. During the forging process, the forging ratio is ≥4, the single deformation of the forging and stretching is 2-5mm, and the total deformation is 40-60%.

[0065] Step S3, cooling after forging: air cooling to above 400°C after forging.

[0066] Step S4, annealing: heating to 860°C according to power, thermal insulation coefficient calculated according to heat penetration of 1h and microstructure transformation rate of 1min / mm, furnace cooling to 650°C and then water cooling for 1.5min to obtain forgings.

[0067] Specifically, the holding time is 1.5 h, and the furnace cooling rate is 65° C. / h.

[0068] Test example:

[0069] The performance of 0Cr13 stainless steel prepared in the first to third embodiments and the comparative example was tested. The specific results are shown in Table 1.

[0070] Table 1

[0071]

[0072]

[0073] Among them, the test method is as follows:

[0074] Room temperature stretching adopts ASTM A370-24 "Standard Test Methods and Definitions for Mechanical Testing of Steel Products", and the equipment uses microcomputer-controlled electronic universal testing machine E45.305 and electronic extensometer Y50 / 10-N.

[0075] 0℃ impact: The impact test adopts ASTM A370-24 "Standard Test Methods and Definitions for Mechanical Testing of Steel Products", and the equipment used is metal pendulum impact tester ZBC2302N-02.

[0076] Hardness: The hardness is measured according to ASTM A370-24 "Standard Test Methods and Definitions for Mechanical Testing of Steel Products", and the Brinell hardness tester EAGLE 3000 is used.

[0077] Metallographic structure: ferrite structure, the microstructure adopts ASTM E407-07 (2015) "Standard Practice for Microetching of Metals and Alloys", the equipment used is Zeiss metallographic microscope AXio vertA1, the magnification is 100X.

[0078] Grain size: The grains are uniformly refined, and the grain size adopts ASTM E112-13 (2021) "Standard Test Method for Determination of Average Grain Size". The equipment used is Zeiss metallographic microscope AXio vertA1 with a magnification of 100X.

[0079] Depend on Figure 2 and Figure 3 It can be found that after the forging process of the present invention is adopted, the ferrite grains are uniformly refined, the grain size is level 7, the carbides are spheroidized and distributed on the ferrite base, and a small amount of chain carbides are precipitated at the grain boundaries. Among them, the gray-white base is ferrite, and black dot-like carbides are distributed on it.

[0080] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0081] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A forging process for ferritic stainless steel, characterized in that: The following steps are involved: Forging heating: heat the test bar to 1100℃~1130℃ with the furnace, keep it warm for 1~2h and then forge it out of the furnace; Forging: Pull the test bar to the set size; Cooling after forging: air cooling to 350-500℃ after forging; Annealing: Heat to 850-870℃ and keep warm according to the power. The insulation coefficient is calculated based on 1h of heat penetration and 1min / mm of microstructure transformation rate. After cooling to 600-700℃, take out of the furnace and water cool for 1-2min to obtain the forging.

2. The forging process of ferritic stainless steel according to claim 1, characterized in that: During the forging process, the forging ratio is ≥4.

3. The forging process of ferritic stainless steel according to claim 2, characterized in that: The single deformation of forging and drawing is 2 to 5 mm, and the total deformation is 40 to 60%.

4. The forging process of ferritic stainless steel according to claim 1, characterized in that: Each time of forging, it is stretched and then rounded.

5. The forging process of ferritic stainless steel according to claim 1, characterized in that: The furnace cooling rate is 50-80℃ / h.

6. The forging process of ferritic stainless steel according to claim 1, characterized in that: The chemical composition of the 0Cr13 stainless steel is as follows by weight percentage: C: ≤0.30%; Si: 0.40-0.80%; Mn: 0.30-1.00%; P: ≤0.30%; S: ≤0.30%; Cr: 11.50-13.50%; Al: ≤0.030%; the remainder is Fe and unavoidable impurities.

7. The forging process of ferritic stainless steel according to claim 6, characterized in that: The chemical composition of the 0Cr13 stainless steel is as follows by weight: C: 0.07-0.08%; Si: 0.56-0.61%; Mn: 0.48-0.53%; P:0.021~0.023%; S: 0.001~0.004%; Cr: 11.76~12.60%; Al: 0.006~0.01%; the balance is Fe and unavoidable impurities.

8. The forging process of ferritic stainless steel according to claim 1, characterized in that: The metallographic structure of the forging is ferrite and bainite, and the grain size is 6 to 8.

9. The forging process of ferritic stainless steel according to claim 1, characterized in that: The room temperature impact of the prepared 0Cr13 ferrite stainless steel is ≥100J, the hardness is 145-186HB, the tensile strength Rm is ≥480MPa, the yield strength Rp0.2 is 280-410MPa, the elongation is ≥35%, and the section shrinkage is ≥72.7%.